H HUBUNGAN KEPEMIMPINAN DENGAN MOTIVASI KERJA TENAGA KESEHATAN DI RUTAN KELAS I MEDAN TAHUN 2021 - MEY INDAH SARI SEMBIRING (Jurnal Kajian Kesehatan Masyarakat, 2023)
Leadership is one of the factors that can affect employee motivation. Motivation is an important thing that is owned by human resources in an organization, because the motivation possessed by individuals can channel, cause, and provide support for individual behavior in working diligently and enthusiastically in achieving the desired results. This study aims to analyze the relationship between aspects of leadership; decision making, direction and guidance, supervision, motivation, and giving awards to the Head of Rutan with the work motivation of health workers in the Medan Class I Detention Center partially. This research is a quantitative research with a survey method with an explanatory research approach. The sample used in this study amounted to 32 people and was collected using a total population sampling technique. The data in this study were collected through interviews and questionnaires. The data in this study were then analyzed using Chi-Square bivariate analysis.The results of this study showed that aspects of leadership; decision-making (p=0,001), direction and guidance (p=0,002), and motivating (p=0,000) affect work motivation of health workers in Rutan Kelas I Medan, while the aspects of leadership; supervision (p=0,118) and awarding (p=0,960) not affecting work motivation of health workers in Rutan Kelas I Medan. Keywords: Leadership, Decision-Making, Direction and Guidance, Supervision, Motivating, Awarding, Work Motivation